Effectiveness of group cognitive behaviour therapy and contribution of positive automatic thoughts in treating depression - Low, Jia Liang (2016)
Depression represents a mental health disorder that has significant repercussions into the lives of its sufferers. The disorder has been the subject of intense scrutiny both worldwide as well as in Malaysia. Efforts are constantly being made to better understand the underlying mechanisms of depression, as well as determining the effectiveness of treatment methods available. Thus the major aims of this thesis are: a) To examine the psychometric properties and factor structure of the Bahasa Malaysia version of the Positive Automatic Thought Questionnaire (ATQ-P-BM), b) To determine the effectiveness of Group Cognitive Behaviour Therapy (GCBT) in the treatment of depression and finally, c) To examine the cognitive mechanism of change in GCBT for depression as well as the contributions of positive automatic thoughts (PAT). In Study 1, a cross-sectional study was used to examine the psychometric properties and factor structures of the ATQ-P-BM. For Study 2 and 3, a randomized, double blind placebo controlled study design was used. Study 1 incorporated both a general population (N=343) and clinical population, whilst Study 2 and 3 only examined the clinical population (N=171). For Study 2 and 3, participants were randomly allocated to the GCBT+TAU, Relaxation+TAU and TAU only group using a random number generator. Participants and clinical psychologists were blinded to the nature of the study. The GCBT+TAU and Relaxation+TAU received eight sessions of GCBT and relaxation training respectively, whilst the TAU only group received treatment as usual (i.e. pharmacotherapy). Trained clinical psychologists administered interventions (GCBT and Relaxation training). For this study, negative life events, positive as well as negative automatic thoughts, depressive symptoms, dysfunctional attitudes and cohesion was measured. Further to that, effect sizes as well as reliably and clinically significant change was determined. Results from Study 1 shows that the ATQ-P-BM endorsed a 5-factor structure model (CMIN/df = 3.58, GFI=0.88, NFI=0.92, CFI = 0.94, RMSEA = 0.07), as well as good psychometric properties (Study 1). In Study 2, results show that GCBT+TAU was able to elicit statistically as well as reliable and clinically significant reductions to depression symptoms. The study also showed that the GCBT+TAU obtained good effect sizes (ηpartial 2=.58) for treatment, greater than that observed in Relaxation+TAU (ηpartial 2=.23) and TAU only treatment group (ηpartial 2=.006). In Study 3, data from a Malaysian populace showed support for a causal mediation model for depression. PAT were found to act as both a mediator and moderator in cognitive models for depression, thus acting as a buffer for the onset of depression. This thesis provided evidence for the application of ATQ-P-BM as a measure of PAT in Malaysia. Results also show that the application of GCBT+TAU is an effective treatment for depression. Analysis of the mechanism of change provided insights into the cognitive changes that occur. Further to that, analysis also provided new insights into PAT regarding its contribution towards treatment and cognitive mechanism of change in GCBT for depression.